If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6 + 2w) + l = 114 Remove parenthesis around (6 + 2w) 6 + 2w + l = 114 Reorder the terms: 6 + l + 2w = 114 Solving 6 + l + 2w = 114 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + l + -6 + 2w = 114 + -6 Reorder the terms: 6 + -6 + l + 2w = 114 + -6 Combine like terms: 6 + -6 = 0 0 + l + 2w = 114 + -6 l + 2w = 114 + -6 Combine like terms: 114 + -6 = 108 l + 2w = 108 Add '-2w' to each side of the equation. l + 2w + -2w = 108 + -2w Combine like terms: 2w + -2w = 0 l + 0 = 108 + -2w l = 108 + -2w Simplifying l = 108 + -2w
| (0.05)7x+36=0.4x+1.2 | | 7/3x-3/4=5 | | X+130=x | | 7/3x-3/4 | | 4x+23=-7 | | -7+4u+u=1 | | 1/4x-5/8x=20-47 | | -7u+4u+u=1 | | 3+6x=3(2x+3) | | 23x-25x=7-9 | | Y-2/X | | 4(3-x)-36=26x-6(4+5x) | | -18m-9=57 | | xsquared+7=23 | | x=3(-5)-2 | | Y-1/X=1/2 | | Y-3/X=4/5 | | 4x+14=3+6x-9 | | X=3(3)-2 | | 00.5(8x+7)=0.6-(x-3) | | X+(X*.82)=1063 | | 2(3t+1)-16=t-(t+13) | | 3(x+9)+x=2(x+5)-8 | | -5x+7=-4(2x+2) | | x+13+x+27=5 | | 8(8t+1)-10=t-(t-1) | | 6666=4 | | (x/x+1)+(x+1/x+2)=1 | | 9(b+6)=9(b-3) | | 3t^2-2t+3=0 | | 9(b+6)=99(b-3) | | 3x-1/5-x-7/10=x-5/4 |